A Comparison of Underage, Young, Middle, and Late Adults in Indicated Prevention Following Impaired Driving. Issue 2 (3rd October 2018) - Schumacher, Julie A.; Stafford, Pamela A.; Beadnell, Blair; Crisafulli, Michele A.
Abstract : The authors examined age differences in baseline features and program response in individuals completing indicated prevention (Prime For Life ® ) for impaired driving. Risk perception, substance use, and support differed by age at baseline and, despite improvements, continued to differ postprogram.